Problems associated with replacing cows in smallholder dairy herds - Dewi, I.A.; Nakokonya, G.; Thorpe, W.R. (British Society of Animal Science, 1998)
Dairy cattle are an important component of farming systems in highland areas of East Africa where they are combined with food an cash crops. The farms are characterised by decreasing size and a small proportion of land used for forage production. Under such conditions only small herds can be maintained. A survey of farms in the Kiambu District of central Kenya in 1996 revealed a median herd size of 2, with 46 percent of farms having only one cow Staal et al (1997). The need to maintain milk supply, and the risk of producing a male calf of little commercial value, result in long lactations and problems of maintaining a sufficient supply of heifers to replace older cows. Analyses were conducted to quantify the problem and to identify the critical intervals within a cow's productive cycle. The number of heifers produced per cow in its lifetime and associated calving intervals were investigated for typical ages at first calving (24, 36 and 48 months), culling age (6-9 years) and calf mortality (10 percent) as observed in the Kiambu survey data. The fact that some calves, particularly those born early or late in the cow's life, may not be viable as replacements was also examined.